2021
DOI: 10.1016/j.jbc.2021.100433
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferase POMGNT1 deficiency strengthens N-cadherin-mediated cell–cell adhesion

Abstract: Defects in protein O -mannosylation lead to severe congenital muscular dystrophies collectively known as α-dystroglycanopathy. A hallmark of these diseases is the loss of the O -mannose-bound matriglycan on α-dystroglycan, which reduces cell adhesion to the extracellular matrix. Mutations in protein O -mannose β1,2-N-acetylglucosaminyltransferase 1 (POMGNT1), which is crucial for the elongation of O -mannosyl glycans, h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…N-Cadherin is modified by Omannoses and N-glycans on distinct peptides. 40 An Nglycosylation analysis by LC-MS/MS of N-cadherin-derived tryptic peptides revealed only a few N-glycosylated peptides in bound and unbound fractions of the lectin affinity (Table S3). However, peptides with oligomannose-type N-glycans were only identified in the bound ConA and BC2L-A fractions.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…N-Cadherin is modified by Omannoses and N-glycans on distinct peptides. 40 An Nglycosylation analysis by LC-MS/MS of N-cadherin-derived tryptic peptides revealed only a few N-glycosylated peptides in bound and unbound fractions of the lectin affinity (Table S3). However, peptides with oligomannose-type N-glycans were only identified in the bound ConA and BC2L-A fractions.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Full-length Mus musculus N-cadherin (CDH1) was cloned in a modified pSecTag B vector containing a C-terminal Strep-and His8-tag as described. 40 Preparation of Lectin Columns. For lectin purification, the BC2L-A plasmid was transformed in Escherichia coli BL21-Gold and cultured in power broth medium with carbenicillin.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, POMGNT1 silencing decreases cell growth and invasion in human glioblastoma cell lines [114]. In this context, it has been recently found that POMGNT1 knockout in the human HEK293T cell line also leads to a lower proliferation and migration rates, in a fashion associated with loss of celllaminin interaction and increase of cell-cell adhesion mediated by N-cadherin [160]. This was attributable to an upregulation of this protein and its encoding mRNA (CDH2 gene) found together with a quantitatively and qualitatively altered N-cadherin N-glycosylation, possibly related to a mildly-decreased MGAT5 expression, encoding the GnT-Va enzyme.…”
Section: Tumor-suppressing or Pro-oncogenic Role Of Dystroglycanopath...mentioning
confidence: 99%
“…This was attributable to an upregulation of this protein and its encoding mRNA (CDH2 gene) found together with a quantitatively and qualitatively altered N-cadherin N-glycosylation, possibly related to a mildly-decreased MGAT5 expression, encoding the GnT-Va enzyme. Also, a sustained activation of the ERK/MAPK pathway was demonstrated, reflected by increased levels of phosphorylated ERK1/2, p38 MAPK and MEK, together with overexpression of a set of EMT-promoting transcription factors, including Snail [160]. These and other molecular events indicative of the occurrence of an EMT-like transition were also evidenced in skin fibroblasts from a MEB patient, harboring a POMGNT1 D179Rfs*11 mutation, this contributing to explain some of his/her clinical DGP symptoms.…”
Section: Tumor-suppressing or Pro-oncogenic Role Of Dystroglycanopath...mentioning
confidence: 99%